Вербалізація концепту «розкіш» в англомовній картині світу - Тумак, Оксана Михайлівна; Tumak, O. М. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті зроблено спробу за допомогою дефініційного та семантико-графічного аналізів здійснити об’єкти¬вацію в англомовній картині світу концепту «розкіш». Автор аналізує й узагальнює роботу відомих лінгвістів над пошуком єдиного визначення концепту. Складено функціонально-семантичне поле вираження досліджу¬ваного концепту, окреслено його домінанту й периферію. Актуальність дослідження визначається загальною направленістю лінгвістичних досліджень у функціональному та когнітивному аспектах. Новизна дослідження полягає в тому, що цей концепт не досліджувався раніше в когнітивно-семантичному аспекті. The article presents an attempt to objectify the concept «luxury» in the English world view by means of definition and semantic graphs analysis. The functional-semantic field of the concept under investigation has been determined, its dominant and periphery have been outlined. The author uses the method of the componential analysis by means of 5 English dictionaries. The semantic field was composed with the help of the semantic graph of the concept under research. The topicality of the research is determined by the overall directedness of linguistic investigations within functional and cognitive frames. The novelty lies in the absence of investigation of the given concept in cognitive-semantic aspects. The perspective of the research lies in the investigation of lexical and semantic combinability of the elements of the given field and peculiarities of verbalization of the concept under investigation.
Verbalization of the Concept «Luxury» in the English World View
Keywords: концепт; concept; концептосфера; conceptosphere; мовна картина світу; language world view